Proliferation-associated miRNAs-494, -205, -21 and -126 detected by in situ hybridization: expression and prognostic potential in breast carcinoma patients - Natalia Gurvits; Tuomo‑Artturi Autere; Heli Repo; Marjukka Nykänen; Teijo Kuopio; Pauliina Kronqvist; Kati Talvinen (Springer Verlag, 2022)
Purpose
To visualize by in situ hybridization (ISH) the levels of a set of proliferation-associated miRNAs and to evaluate their impact and clinical applicability in prognostication of invasive breast carcinoma.
Methods
Tissue specimen from breast carcinoma patients were investigated for miRNAs-494, -205, -21 and -126. Prognostic associations for levels of miRNAs were analyzed based on complete clinical data and up to 22.5-year follow-up of the patient material (n = 285). For detection of the miRNAs, an automated sensitive protocol applying in situ hybridization was developed.
Results
MiRNA-494 indicated prognostic value for patients with invasive breast carcinoma. Among node-negative disease reduced level of miRNA-494 predicted 8.5-fold risk of breast cancer death (p = 0.04). Altered levels and expression patterns of the studied miRNAs were observed in breast carcinomas as compared to benign breast tissue.
Conclusions
The present paper reports for the first time on the prognostic value of miRNA-494 in invasive breast cancer. Particularly, detection of miRNA-494 could benefit patients with node-negative breast cancer in identifying subgroups with aggressive disease. Based on our experience, the developed automatic ISH method to visualize altered levels of miRNAs-494, -205, -21 and -126 could be applied to routine pathology diagnostics providing that conditions of tissue treatment, especially fixation delays, are managed.